PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Konsumen Paras Snack Di Kabupaten Boyolali Tahun 2019) - Isnaini Sholikah; Unna Ria Safitri; A. Fidhdiarr Ariestanto T N K (Universitas Boyolali, 2020)
The research objective is to determine the effect of price, location, and service quality variables on customer satisfaction. 100 respondents who were used as samples were involved in filling out the questionnaire, taken from Paras Snack consumers. Collecting data using questionnaires with the Accidential Sampling Method, and analysis using quantitative methods. The validity and reliability tests were used in the data instrument testing, and the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test were used to analyze the data, the t test and F test and the determination test (R2) were used to test the hypothesis. Validity test, reliability test and classical assumption test whose data have been met are then processed to produce a regression equation: Y = 4,475 + 0.126 X1 + 0.348 X2 + 0.374. Partially service quality variables do not affect customer satisfaction variables, while variables that affect customer satisfaction partially are price and location variables as indicated by hypothesis testing using the t-test. Then the results of the F test are shown simultaneously the influence of the three independent variables on the dependent variable. It is stated from the results of the determination test (R2) that the value of the Adjusted R Square is 0.811, which means that the dependent variable of customer satisfaction with a value of 81.1% can be explained by the three independent variables, namely the variable price, location and service quality and the remaining 18.9% value is explained by the variable outside of research.